2015
DOI: 10.1016/j.febslet.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation inSaccharomyces cerevisiae is regulated by RNA/DNA helicase Sen1p

Abstract: a b s t r a c tThe Nrd1-Nab3-Sen1 (NNS) complex terminates transcription of non-coding RNA genes and mediates degradation of the produced transcript by the nuclear exosome. The NNS complex also represses some stress response genes, by stimulating premature termination. A well-characterized stress response in yeast is flocculation, where cells aggregate to form flocs under expression of lectin-encoding genes designated as FLOs. In this study, we demonstrated the role of the NNS complex and Rrp6p in the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…Previous work by our group has shown constitutive expression of FLO genes in the Sen1 , Nab3 mutants and rnt1Δ cells leading to calcium‐dependent flocculation/aggregation of cells (Singh et al , ). Later, another study showed expression of the FLO1 gene in the Sen1 mutant (Chen et al , ).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Previous work by our group has shown constitutive expression of FLO genes in the Sen1 , Nab3 mutants and rnt1Δ cells leading to calcium‐dependent flocculation/aggregation of cells (Singh et al , ). Later, another study showed expression of the FLO1 gene in the Sen1 mutant (Chen et al , ).…”
Section: Discussionmentioning
confidence: 90%
“…We focused our studies to find whether or not flocculation phenotype is connected with cellular morphology, cell wall composition and growth in response to cell wall damaging agents. Previously, we established that the de‐repression of FLO genes in Sen1 , Nab3 and Rnt1 mutants lead to flocculation phenotype (Singh et al , ). One recent report (Chen et al , ) has also shown up‐regulation of FLO1 mRNA in Sen1 mutant strain suggesting the contribution of Sen1 in the regulation of flocculation phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations